Do Intellectual Capital in the Relationship between Governance and Corporate Financial Performance, Strengthening or Weakening? - Wulansuci, Rohmah; Sugeng, Bambang; Sidharta, Eka Ananta (International Journal of Business, Law, and Education, 2024)
This study aims to identify and analyze the role of intellectual capital as a moderating variable in the relationship between governance and firm financial performance. Using panel data regression, this study analyses 412 observation units from 103 manufacturing companies listed on the Indonesia Stock Exchange during 2018-2021. The results show that, partially, both governance and intellectual capital have no significant effect on financial performance. However, when the governance variable has interacted with intellectual capital and a moderation test is conducted, it is found that the interaction variable has a significant effect on financial performance with a positive coefficient. This indicates that intellectual capital acts as a pure moderator variable of the positive effect of governance on financial performance. This result implies that in the absence of high intellectual capital, governance proves to be inefficient in its efforts to improve the firm's financial performance